Sociodemographic Factors Associated with Purchasing Frozen, Fresh, Canned, and Dried Produce in a Nationally Representative Sample of United States Households - Graham E Bastian; Joslyn K Russell; Annie J Roe; Raveen Rani (Current Developments in Nutrition)
Background: Frozen fruits and vegetables (FV) are convenient, cost-effective, reduce food waste, and can be just as nutritious as their fresh counterparts. Despite these numerous advantages, it is unclear which consumer segments are more likely to purchase frozen FV, especially compared with fresh, canned, or dried FV, which could help inform targeted nutrition education interventions. Objective: The objective of this study is to explore sociodemographic factors associated with increased or decreased odds of purchasing frozen, fresh, canned, and dried FV in a nationally representative sample. Methods: A secondary data analysis was conducted using publicly available data from the nationally representative 2021 United States Bureau of Labor Statistics Consumer Expenditure Diary Surveys, in which participants were instructed to record all household expenditures during a 2-wk timeframe. Chi-square analyses and unadjusted and adjusted logistic regressions were used to explore the associations between the included sociodemographic variables and FV purchasing. Results: Of the final sample (n = 6028), 230 purchased frozen fruits and 1163 purchased frozen vegetables during the study period. Households with higher income, higher educational attainment, and more children <18 y had higher odds of purchasing any type of FV. Households utilizing the Supplemental Nutrition Assistance Program (SNAP) had higher odds of purchasing frozen vegetables after controlling for other variables (odds ratio: 1.24, 95% confidence interval: 0.99, 1.56, P = 0.07). Compared with White non-Hispanic-led households, Asian- and Hispanic-led households had higher odds of purchasing fresh FV and lower odds of purchasing frozen vegetables. Conclusions: The results of this exploratory study could inform future research, particularly regarding the factors that influence the frozen FV perceptions of SNAP consumers and Hispanic and Asian households. Since nutrition educators who teach SNAP participants already promote frozen FV, studies that investigate how SNAP consumers’ perceptions change because of such interventions are also warranted.